DesignWork : a study of public works programmes in South African architectural projects - Splaingard, Daniel (School of Architecture, Planning and Geomatics, 2016)
Increasingly in South Africa, architects are requested to design buildings that meet the job-creation and training goals of the Expanded Public Works Programme (EPWP), a government-led poverty relief initiative. In so doing, they have a mandate both to design buildings and to design work for the poorest of the poor. This unique context of architectural practice is herein termed DesignWork, and the links between these designs and their measurable work outcomes will be the focus of this Case Study Research. Architects can be key agents in shaping economic empowerment for participants and architectural quality within these projects. This thesis investigated how architects addressed three key goals of increasing wage transfer through labour-intensive construction, enabling skill development through relevant in-situ technical training, and creating quality assets. With the 2030 National Development Plan anticipating the growth of the EPWP in the coming decades, the development of effective architectural strategies within this context is of great significance. Evidence from semi-structured interviews, site visits, archival documents, direct observation, and data collection were used to interrogate the architectural design strategies and work outcomes within two select projects. What emerges is a focused view of the central challenges of achieving the EPWP programme goals, baseline data for future research, and an understanding of the foreseeable challenges for architects designing in this context.